Safety and Efficacy of Pulsed‐Field Ablation With a Pentaspline Ablation Catheter Versus Cryoablation for Atrial Fibrillation: A Systematic Review and Meta‐Analysis - Yi Cai; Hao Chen; Miao‐Fu Li; Yi‐Zhou Xu (Clinical Cardiology, 2026)
ABSTRACT Background Pulsed‐field ablation (PFA) is an emerging technology for atrial fibrillation (AF) ablation. However, there is few studies comparing the clinical advantages and disadvantages of PFA and cryoballoon ablation (CBA). This study aimed to perform a comprehensive meta‐analysis to evaluate the efficacy and safety of PFA using a pentaspline ablation catheter compared with CBA for treating AF. Methods This study was registered in the International Prospective Register of Systematic Reviews (ID: CRD420251061599). Studies comparing PFA using a pentaspline ablation catheter with CBA for pulmonary vein isolation (PVI) were systematically searched from database inception to March 2025. Results Six trials involving 2024 patients were included. No significant difference was observed in atrial tachyarrhythmia recurrence between PFA and CBA (OR) = 0.71; 95% confidence interval (CI): 0.48 to 1.06). However, in patients with paroxysmal AF, the PFA group exhibited a lower incidence of AT recurrence (OR = 0.62; 95% CI: 0.46 to 0.85). PFA was superior to CBA in terms of ablation time (MD) = −14.12; 95% CI: −16.31 to −11.93) and left atrial dwell time (MD = −9.44; 95% CI: −15.69 to −3.19). Hypersensitive troponin release was higher in the PFA group (MD = 547.29; 95% CI: 53.55 to 1041.03), while CBA was associated with a higher incidence of phrenic nerve palsy (OR = 0.06; 95% CI: 0.01 to 0.30). Conclusion PFA demonstrates superior safety and efficacy compared with CBA for PVI in patients with AF. These findings provide additional procedural options for patients and electrophysiologists in clinical practice.